“They look better on the breasts”: Advertisement, sexuality, and the bra business in postsocialist Poland - Marta Chmielewska (Connexe, 2023)
This article examines the 1990s transition from socialism to capitalism in Poland through the lens of the changing market of underwear. Based on oral history interviews, archival research of bra production companies, as well as an analysis of contemporary press reports, I examine how the integration of the Polish economy into the global capitalist system post 1989 influenced its sexual culture. This article shows how the end of the public sector’s monopoly on the production of underwear and the rise of the private sector introduced new form of bras that were codified as sexual by the media and manufacturers themselves. These new types of products mimicked Western European brands, distancing themselves from the socialist era underwear, and incorporated new technology designed to model and discipline female bodies. Through a deep analysis of a 1996 article on the bra business from The Electoral Gazette [Gazeta Wyborcza], the biggest daily newspaper in Poland, I show how the liberal media were ambivalent to such changes and portrayed it as differences between generations of women in the face of calls for stricter censorship from conservative politicians and the Catholic Church.